The Opportunity and Basic Principles of Ecotourism - Dilmonov Qudrat Baxtiyorovich (International Journal on Economics, Finance and Sustainable Development (IJEFSD), 2021)
This article analyzes the opportunity and basic principles of ecotourism. Ecotourism is based on the principles of sustainable tourism, taking into account its impact on economic, social and natural environment. Eco-tourism also includes the following specific principles which distinguish it from the wider concept of sustainable tourism: Actively contribute to the conservation of natural and cultural heritage; involvement of local and indigenous communities in the planning, development and implementation of eco-tourism activities, which contributes to their well-being; clarification of the tour value of natural and cultural heritage centers visited tour